14 Signatures of pre-natal nutrition in cattle: adaptations in DNA methylation, gene expression, and post-natal growth. (7th December 2018) - Fitzsimmons, C; Devos, J; Li, C; Paradis, F; Straathof, C; Penner, G; Hare, K; McKinnon, J; Añez-Osuna, F; Block, H; Colazo, M; Bruce, H
Abstract: Exploring pre-natal nutrition to modulate and improve post-natal growth and development in cattle continues to reveal new opportunities for researchers, and ultimately cattle producers. Effects of pre-natal dietary interventions have been shown to be markedly time- and treatment-specific, although a few particular patterns of changes in post-natal growth present themselves recurrently. Male calves, both bulls and steers, appear to be more susceptible to alterations in pre-natal maternal nutrition and, when the opportunity presents, turn it into increased growth performance at a later stage of life (Fitzsimmons unpublished, Añez-Osuna et al. 2018). Male calves may also develop differences in growth patterns in association with pre-natal nutrition even if no differences in weight are detected at birth. Elucidating the how and why behind these changes is more challenging, as well as any long-term effects upon animal health and longevity. Examination of gene expression patterns within tissues that are highly connected with growth and metabolism in cattle, for example skeletal muscles and liver, shows that expression of genes connected to overall growth such as the IGF family, myogenesis ( MYOD1, MYOG, etc.), adipogenesis ( PPARG ), as well as microRNAs that modulate proliferation and differentiation in skeletal muscle, can be associated with pre-natal maternal diet (Paradis et al. 2017). Furthermore, DNA methylation patterns of differentially-methylated regions (DMRs) near the genes for IGF2 and IGF2R in the bovine have been found to be significantly associated with pre-natal maternal diet, and the degree of methylation of IGF2 DMR2 to be negatively correlated with IGF2 expression (Paradis et al. 2017, Fitzsimmons et al. 2017). Dissecting the causes and effects of these associations still presents a great challenge, but the possibility of explaining more of the 'E' in the classic equation of Phenotype = Genotype (G) + Environment (E) + G X E is a fascinating and exciting opportunity.